The Use of Telegram Based E-learning for English Language Learning during The Covid 19 Pandemic - Qorina Aulia Syifa (Universitas Lambung Mangkurat, 2022)
During this Covid-19 pandemic, technology is widely used, including in the world of education. All schools in the world are forced to use E-learning as their teaching. With the media, it will make learning easier during this pandemic. Researchers use the Tiktok application as a learning medium to find out how students and teachers perceive the use of Telegram with Telegram BOT in learning English. The use of telegram BOT certainly makes it easy for students to receive material and the teacher is easy to develop material in the form of video and audio with a longer duration. In this study, the researcher used a qualitative method. The researcher uses descriptive qualitative research to analyze the data, there are four activities to analyze: data reduction, word presentation and conclusion drawing. Researchers took samples from 2 students of class VII SMP IT INSAN HARAPAN. The results showed that using telegram bots made it easier for students to learn English material delivered by the teacher.